2023
DOI: 10.3389/fchem.2023.1166313
|View full text |Cite
|
Sign up to set email alerts
|

Spatial sterol metabolism unveiled by stimulated Raman imaging

Abstract: Graphical AbstractHigh-resolution stimulated Raman scattering (SRS) imaging of a genetically engineered model (GEM) enables metabolite imaging in a yeast model and uncovers an unexpected regulatory mechanism of sterol metabolism, providing new insights underpinning the distributional and functional importance of sterol in cells. SRS-GEM demonstrates a promising platform to explore unknown metabolic mechanisms beyond the reach of conventional approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Finally, the MDA-MB-231 cells were washed with PBS and immersed in PBS for SRS imaging. SRS imaging was performed on a picosecond SRS microscope [16] . An ultrafast laser system with dual output at 80 MHz (picoEmerald; Applied Physics & Electronics, Berlin, Germany) provided both pump (tunable wavelength 700‒990 nm) and Stokes beams (fixed wavelength 1031 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the MDA-MB-231 cells were washed with PBS and immersed in PBS for SRS imaging. SRS imaging was performed on a picosecond SRS microscope [16] . An ultrafast laser system with dual output at 80 MHz (picoEmerald; Applied Physics & Electronics, Berlin, Germany) provided both pump (tunable wavelength 700‒990 nm) and Stokes beams (fixed wavelength 1031 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Through SRS imaging for sterol characteristic peak at 2870 cm −1 and lipid characteristic peak at 2850 cm −1 , spatial sterol metabolism was visualized in yeast. 83 The Raman signal at ∼3010 cm −1 corresponds to = C−H bonds, allowing visualization of unsaturated lipid distribution and quantifying lipid unsaturation degrees. Building on this, Jia et al conducted two-color SRS imaging at 2850 and 3010 cm −1 in fibrotic liver tissues, revealing a location-specific increase of unsaturated triglycerides during fibrosis.…”
Section: Multispectral Crs Imagingmentioning
confidence: 99%
“…Yoshifumi et al demonstrated multispectral SRS imaging in Euglena gracilis by reducing the number of spectral points to 4, selecting characteristic peaks at 2850 cm –1 , 2910 cm –1 , 2937 cm –1 , and 3050 cm –1 , to decompose the distribution of lipids, paramylon, chlorophyll II, and protein/nucleic acid in single cells (Figure A, B ) . Through SRS imaging for sterol characteristic peak at 2870 cm –1 and lipid characteristic peak at 2850 cm –1 , spatial sterol metabolism was visualized in yeast . The Raman signal at ∼3010 cm –1 corresponds to = C–H bonds, allowing visualization of unsaturated lipid distribution and quantifying lipid unsaturation degrees.…”
Section: Crs Imaging Strategies For Lipidsmentioning
confidence: 99%